PELAKSANAAN PEMBERIAN HAK ASIMILASI BAGI NARAPIDANA DI RUTAN KLAS II-B PINRANG - Tampa, Abd Rahman (PETITUM, 2014)
Implementation of Assimilation Granting Rights for Prisoners in Detention Pinrang Class II-B. (Supervised by Rachmad Baro and Amiruddin) .This thesis research is intended to study and analyze the implementation of the Provision of asimilation rights of prisoners in the House of Detention Class II-B Pinrang, and knowing inhibiting factors in implementing the assimilation rights award. This study uses the technique of collecting data from respondents include direct interviews with the Head of Development Rutan, with secondary data such as file list of inmates who acquire rights assimilation 2009 materials. The data were found to indicate that the implementation of the provision of Assimilation Rights in Detention Class II-B Pinrang procedure has met the requirements both substantive and administrative requirements. The detention program that supports the assimilation Rights Award is a program of coaching education, spirituality and skills. Assimilation rights provision limiting factor is the infrastructure factors, family and local residents and urban factors.